Dignity rights : courts, constitutions, and the worth of the human person - Daly, Erin (Democracy, citizenship, and constitutionalism., 2013)
With cases from around the world on a wide range of subjects including prison conditions, employment, sexuality, reputation, and death, this ground-breaking book examines how judicial interpretations of dignity redefine what it means to be human in the modern world.